2012
DOI: 10.1002/vnl.20291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of commercial fillers by recycled poly(ethylene terephthalate) powder on the properties of natural rubber composites

Abstract: Commercial fillers, including carbon black (N550), halloysite nanotubes (HNTs), and precipitated silica, were replaced by recycled poly(ethylene terephthalate) powder (R‐PET) in natural rubber (NR) composites. Five different compositions of NR/N550/R‐PET, NR/HNTs/R‐PET, and NR/silica/R‐PET compounds, i.e., 100/20/0, 100/15/5, 100/10/10, 100/5/15, and 100/0/20 parts per hundred rubber (phr), were prepared on a two‐roll mill. The curing behavior, tensile properties, and morphological characteristics of the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…The improvement of tensile strength is attributed to the geometrical structure of HNTs because the HNTs have a tubular nanostructure, a large aspect ratio , and high strength, stiffness, and modulus of HNTs . In addition, the uniform dispersion of HNTs in the polymer matrix also enhances the tensile strength of the composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of tensile strength is attributed to the geometrical structure of HNTs because the HNTs have a tubular nanostructure, a large aspect ratio , and high strength, stiffness, and modulus of HNTs . In addition, the uniform dispersion of HNTs in the polymer matrix also enhances the tensile strength of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of waste materials into the polymer composite has been widely reported . One of the waste materials is natural rubber (NR) gloves.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic mechanical thermal analysis showed that the prepared materials have similar glass transition temperatures. However, increase in the content of titanium dioxide in the obtained materials is connected with higher energy 1 3 Fillers are incorporated into rubber compounds to improve processability, cost reduction, and physical properties modifying the composites [11,12]. One of the most important reasons for filler addition is related to make the production of the final product more economical [11].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of cross‐linking NRL‐compatibilized blends is believed to account for the increases in M100 and hardness. It has been reported elsewhere that the modulus is an inverse function of elongation at break. The characteristics which improve elongation at break also act to reduce the modulus of rubber vulcanizate.…”
Section: Resultsmentioning
confidence: 84%